The terrorist - Cooney, Caroline B. (New York : Scholastic, 1997)
Sixteen-year-old Laura, an American living in London, tries to find the person responsible for the death of her younger brother Billy, who has been killed by a terrorist bomb.
710
Accelerated Reader AR
Keywords: Terrorism -- Fiction; Mystery and detective stories; London (England) -- Fiction